Ti–Zr–Si–Nb Nanocrystalline Alloys and Metallic Glasses: Assessment on the Structure, Thermal Stability, Corrosion and Mechanical Properties - Gabor, Camelia; Cristea, Daniel; Velicu, Ioana-Laura; Bedo, Tibor; Gatto, Andrea; Bassoli, Elena; Varga, Bela; Pop, Mihai Alin; Geanta, Victor; Stefanoiu, Radu; Codescu, Mirela Maria; Manta, Eugen; et al. (MDPI AG, 2019)
The development of novel Ti-based amorphous orβ-phase nanostructured metallic materials could have significant benefits for implant applications, due to improved corrosion and mechanical characteristics (lower Young’s modulus, better wear performance, improved fracture toughness) in comparison to the standardized α+β titanium alloys. Moreover, the devitrification phenomenon, occurring during heating, could contribute to lower input power during additive manufacturing technologies. Ti-based alloy ribbons were obtained by melt-spinning, considering the ultra-fast cooling rates this method can provide. The titanium alloys contain in various proportions Zr, Nb, and Si (Ti60Zr10Si15Nb15, Ti64Zr10Si15Nb11, Ti56Zr10Si15Nb19) in various proportions. These elements were chosen due to their reported biological safety, as in the case of Zr and Nb, and the metallic glass-forming ability and biocompatibility of Si. The morphology and chemical composition were analyzed by scanning electron microscopy and energy-dispersive X-ray spectroscopy, while the structural features (crystallinity, phase attribution after devitrification (after heat treatment)) were assessed by X-ray diffraction. Some of the mechanical properties (hardness, Young’s modulus) were assessed by instrumented indentation. The thermal stability and crystallization temperatures were measured by differential thermal analysis. High-intensity exothermal peaks were observed during heating of melt-spun ribbons. The corrosion behavior was assessed by electrocorrosion tests. The results show the potential of these alloys to be used as materials for biomedical applications.
Keywords: biocompatibility; melt spinning; amorphous titanium alloy; thermal stability